ANALISIS TENTANG KEPERCAYAAN DIRI SISWA KELAS 6 SD GUGUS TERATAI PUTIH KECAMATAN KUBU TAHUN PELAJARAN 2013/2014 - Nurialinda '; Abu Asyari Abu Asyari; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This study, entitled "Analysis of Confidence Grade 6 elementary Force White Lotus Kubu district academic year 2013/2014". Based on the observations made, it was found most students do not dare to express an opinion, an officer bandera apples and imitate what the result of his employment when given tugas.Tujuan this study were 1) to determine the image confidence 6th grade students. 2) To know the description of confidence confidence 6th grade students Ethnic Malays. 3) To know the picture of confidence 6th grade students Javanese.The method used in this research is descriptive method. The population in this study is a 6th grade student Force White Lotus Kubu district and use techniques saturated samples. Accurating yiel as follows 1) the picture of confidence 6th grade students are in the weak category. 2) Overview confidence 6th grade students Ethnic Malays in category lemah. 3) Image confidence 6th grade students in Java Ethnic weak category. While the category of very strong, strong, strong average, and the average is weak not found. Weak confidence 6th grade students found on the indicator control of feeling, for 6th grade students of ethnic malays are found in indicators worried and afraid to face a variety of situations, and for 6th grade students of ethnic javanese found on the feeling of control indicator. Weak confidence 6th grade students clusters White Lotus Kubu subdistrict thought to be caused by several factors, such as parental education students, students' parents work, the environment (which consists of family, school, and community), life experiences, and the instrument used not according to the respondents. Keywords: Students Confidence.